Molecular epidemiology and clinical features of Klebsiella variicola bloodstream infection compared with infection with other Klebsiella pneumoniae species complex strains - Tatsuya Ohno; Sohei Harada; Hiroki Saito; Rimi Tanii; Kohji Komori; Miki Kurosawa; Haruaki Wakatake; Minoru Kanazawa; Uiri Ohki; Ayu Minoura; Mario Yamada; Satsuki Kaneko; et al. (Microbiology Spectrum)
ABSTRACT Klebsiella variicola is an emerging pathogen within the Klebsiella pneumoniae species complex, and its clinical and microbiological characteristics remain poorly understood. This retrospective case-control study analyzed 252 patients with bloodstream infections caused by K. pneumoniae species complex, including 60 with K. variicola infection, to elucidate these characteristics. Our study showed no significant differences in clinical outcomes, such as 30-day mortality, between K. variicola and K. pneumoniae. However, a significant difference was found in the rate of harboring [peg-344, iucA, and rmpA] genes, which are associated with virulence in K. pneumoniae, suggesting that K. variicola may be generally less virulent. Notably, we identified two patients with community-acquired liver abscess caused by hypervirulent K. variicola, representing the first genetically analyzed case of this phenomenon in Japan and highlighting the potential virulence of this species. While there have been several reports on K. variicola carrying hypervirulence genes, this is the first report in Japan, to our knowledge, to genetically characterize a hypervirulent K. variicola isolated from a patient with disseminated liver abscesses using whole-genome sequencing. Multilocus sequence typing revealed high diversity among K. variicola isolates, with 49 distinct sequence types identified, 30 of which were newly registered, highlighting the genetic heterogeneity of this pathogen. No significant clinical differences were observed between K. variicola and other Klebsiella spp. The emergence of hypervirulent K. variicola strains with the potential to cause severe complications warrants further surveillance and research.IMPORTANCEKlebsiella variicola is increasingly recognized as an emerging pathogen commonly found in the environment and human gut. However, its clinical and microbiological characteristics remain poorly understood. This study provides a comprehensive analysis of K. variicola bloodstream infections (BSIs), comparing clinical and genetic features with the closely related K. pneumoniae. We identified significant differences in the prevalence of virulence genes between the two species. Notably, we observed K. variicola causing disseminated liver abscesses, similar to hypervirulent K. pneumoniae strains. These findings have important implications for accurate species identification, informing treatment strategies, and improving patient outcomes in the face of this emerging infectious threat.